Integration of Different Graphene Nanostructures with PDMS to Form Wearable Sensors - Shan He; Yang Zhang; Jingrong Gao; Anindya Nag; Abdul Rahaman (Nanomaterials, 2022)
This paper presents a substantial review of the fabrication and implementation of graphene-PDMS-based composites for wearable sensing applications. Graphene is a pivotal nanomaterial which is increasingly being used to develop multifunctional sensors due to their enhanced electrical, mechanical, and thermal characteristics. It has been able to generate devices with excellent performances in terms of sensitivity and longevity. Among the polymers, polydimethylsiloxane (PDMS) has been one of the most common ones that has been used in biomedical applications. Certain attributes, such as biocompatibility and the hydrophobic nature of PDMS, have led the researchers to conjugate it in graphene sensors as substrates or a polymer matrix. The use of these graphene/PDMS-based sensors for wearable sensing applications has been highlighted here. Different kinds of electrochemical and strain-sensing applications have been carried out to detect the physiological signals and parameters of the human body. These prototypes have been classified based on the physical nature of graphene used to formulate the sensors. Finally, the current challenges and future perspectives of these graphene/PDMS-based wearable sensors are explained in the final part of the paper.